2011
DOI: 10.1007/s11242-011-9867-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM

Abstract: The present study is intended to study heat and mass transfer in a vertical annular cylinder embedded with saturated porous medium. The inner surface of cylinder is maintained at uniform wall temperature and uniform wall concentration. The governing partial differential equations are non-dimensionalised and solved by using finite element method (FEM). The porous medium is discritised using triangular elements with uneven element size. Large number of smaller-sized elements are placed near the walls of the annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…draws the conclusion of Lewis number (Le) As observed in case of heat and mass transfer[12], Lewis number influences the mass transfer substantially. This is obvious from present case (figure 4), that shows highly distorted iso-concentration lines as compared to isotherms, when Lewis number (Le) is increased from 1 to 25.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…draws the conclusion of Lewis number (Le) As observed in case of heat and mass transfer[12], Lewis number influences the mass transfer substantially. This is obvious from present case (figure 4), that shows highly distorted iso-concentration lines as compared to isotherms, when Lewis number (Le) is increased from 1 to 25.…”
mentioning
confidence: 65%
“…The literature reveals that various heat transfer characteristics of porous cavities have been investigated and reported by many researchers. For instance, the heat transfer has been investigated in porous cavities and porous annulus by applying hot temperature at left vertical wall and maintaining cold temperature at the right wall [7][8][9][10][11][12][13]. This included the investigation of heat transfer along with difficult boundary conditions or various other phenomenon such as viscous irregular cavity [7], viscous dissipation [8][9][10], Soret and Dufor effect [11], heat and mass transfer [12] , the effect of heat generating strip placed inside the porous cavity [13], wavy tube heat exchanger [14], flow of nanofluid inside the porous media [15][16][17] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of heat transfer in regular porous cavity (Jecl and Kerget, 2003; Bahloul, 2006; Saeid and Pop, 2004; Badruddin et al , 2006a, 2007a; Sharif and Mohammad, 2005; Nazari et al , 2015) has been the best choice of research for many researchers, probably because of its applications as well as simple geometry and boundary conditions involved, making it relatively easy to analyze. It is also notable that porous medium confined in the cylindrical geometry with axisymmetric boundary condition can also be treated as cavity (Rajamani et al , 1995; Prasad and Kulacki, 1984; Badruddin et al , 2012a, 2012b, 2012c; Ahmed et al , 2011, 2014) with proper care of governing equations. The increased complexity either in porous geometry or the boundary conditions is somewhat involved process.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that there has been renewed interest to study the uncommon or irregular shapes of cavity containing the porous medium. For instance, there have been studies conducted with respect to the square porous annulus (Badruddin et al , 2012a, 2012b; Nik-Ghazali et al , 2014; Ebaid and Bataresh, 2017). It was found that the temperature in such cavities exhibits peculiar behavior with Nusselt number showing dependence on the length of internal boundary.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, one must be aware of two fundamental points: first, it does not calculate exact solutions but approximate ones; second, it discretizes the problem by representing functions by a finite number of values, that is, to move from the “continuous” to the “discrete”. There are numerous methods for the numerical approximation of PDEs, among them, popularly adopted are finite element method (Lewis and Garner, 1972; Strada and Lewis, 1980; Morgan et al , 1984; Tadayon et al ,1987; Ahmed et al , 2011; Ahmed et al , 2009; Badruddin et al , 2006a, 2006b, 2007a, 2007b, 2012a, 2012b, 2012c; Li and Rui, 2015; Sajid et al , 2008; Balla and Kishan, 2015; Wansophark et al , 2005) finite difference method (Achemlal and Sriti, 2015; del Teso, 2014; Oka et al , 1994; Rui and Liu, 2015; Liu and Yuan, 2008; Sheremet and Pop, 2014; Chamkha and Muneer, 2013; Sheremet, 2015) and finite volume method (Dotlić, 2014; Kumar, 2012). These finite element, finite difference and finite volume methods require that each PDE be converted into its equivalent set of algebraic equations that depends on the number of elements into which the physical domain is divided.…”
Section: Introductionmentioning
confidence: 99%